Decomposition of a Petri Net-Based Cyber-Physical System toward Implementation as an Integrated System within FPGA - Wiśniewski, Remigiusz (2023)
This research was funded by NATIONAL SCIENCE CENTRE, POLAND, grant number 2019/35/B/ST6/01683. The APC was funded by A. Costa and R. Wisniewski. Publisher Copyright: © 2023 by the authors.